Tax Avoidance pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2019-2023 - Natasya Wahyu Utami; Indah Kurniyawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of transfer pricing, thin capitalization, capital intensity and audit quality on tax avoidance. The population in this study are companies that have been listed on the Jakarta Islamic Index (JII) during the 2019-2023 period, totaling 54 companies. The sample in this study amounted to 19 multinational companies or 95 observation data determined by purposive sampling method. The data analysis used is multiple linear regression analysis with dummy variables with the SPSS 29 program. The results showed that transfer pricing partially had a negative and significant effect on tax avoidance, while thin capitalization, capital intensity and audit quality partially have no significant effect on tax avoidance. However, transfer pricing, thin capitalization, capital intensity and audit quality simultaneously have a positive and significant effect on tax avoidance.